Linear Polyurethanes : Synthesis Methods, Chemical Structures, Properties and Applications. - Krol, Piotr (BRILL, 2008)
This publication is a study based on the authora (TM)s own research articles as well as on recent literature on linear polyurethanes. The book provides an insight in essential aspects of the process kinetics of polyaddition and its synthetic consequences. These are of great importance for contemporary applications in linear polyurethanes, such as biomedical materials, elastomers, foams, adhesives and coatings.